Use of a Participatory Method for Community-Based Brucellosis Control Design in Agro-Pastoral Areas in Tanzania - Asakura, Shingo; Makingi, George; John, Kunda; Kazwala, Rudovick; Makita, Kohei (Frontiers in Veterinary Science, 2022)
Brucellosis is widespread in both humans and livestock in many developing countries. The authors have performed a series of epidemiological studies on brucellosis in agro-pastoral areas in Tanzania since 2015, with the aim of the disease control. Previously, the potential of a community-based brucellosis control initiative, which mainly consisted of the sale of cattle with experience of abortion and vaccinating calves, was assessed as being effective and acceptable based on a quantitative approach. This study was conducted to investigate the feasibility of community-based brucellosis control program using participatory rural appraisals (PRAs) and key-informant interviews. Four PRAs were performed together with livestock farmers and livestock and medical officers in 2017. In the PRAs, qualitative information related to risky behaviors for human infection, human brucellosis symptoms, willingness to sell cattle with experience of abortion, and willingness to pay for calf vaccination were collected, and a holistic approach for a community-based disease control project was planned. All of the communities were willing to implement disease control measures. To avoid human infection, education, especially for children, was proposed to change risky behaviors. The findings of this study showed that community-based disease control measures are promising.